Results of Determining The Number of Machine-Tractor Aggregates Used in Preparing Soil Plowed in Autumn by The Traditional Method for Sowing - Vakhobovich, Sobirov Rasulbek (American Journal of Botany and Bioengineering, 2026)
This article examines the issues of determining the number of machine-tractor units used in preparing autumn plowed soil for sowing and evaluating their efficiency. The study compared traditional and combined processing methods and determined the optimal composition of the units. As a result of calculations, it was established that the use of combined units allows for the efficient use of tractor power and reduces labor and fuel consumption. It is also substantiated that reducing the number of field passes reduces soil compaction. The number of technical means required to prepare 1,000 hectares of land for sowing within the established agrotechnical timeframe has been calculated. The research results showed that the use of combined machines is more economically and operationally efficient. The article serves to improve the effective use of agricultural machinery and soil cultivation technologies.